Voice deviation, dysphonia risk screening and quality of life in individuals with various laryngeal diagnoses (Clinics, 2018)
OBJECTIVES: To characterize the voice quality of individuals with dysphonia and to investigate possible correlations between the degree of voice deviation (D) and scores on the Dysphonia Risk Screening Protocol-General (DRSP), the Voice-Related Quality of Life (V-RQOL) measure and the Voice Handicap Index, short version (VHI-10). METHODS: The sample included 200 individuals with dysphonia. Following laryngoscopy, the participants completed the DRSP, the V-RQOL measure, and the VHI-10; subsequently, voice samples were recorded for auditory-perceptual and acoustic analyses. The correlation between the score for each questionnaire and the overall degree of vocal deviation was analyzed, as was the correlation among the scores for the three questionnaires. RESULTS: Most of the participants (62%) were female, and the mean age of the sample was 49 years. The most common laryngeal diagnosis was organic dysphonia (79.5%). The mean D was 59.54, and the predominance of roughness had a mean of 54.74. All the participants exhibited at least one abnormal acoustic aspect. The mean questionnaire scores were DRSP, 44.7; V-RQOL, 57.1; and VHI-10, 16. An inverse correlation was found between the V-RQOL score and D; however, a positive correlation was found between both the VHI-10 and DRSP scores and D. CONCLUSION: A predominance of adult women, organic dysphonia, moderate voice deviation, high dysphonia risk, and low to moderate quality of life impact characterized our sample. There were correlations between the scores of each of the three questionnaires and the degree of voice deviation. It should be noted that the DRSP monitored the degree of dysphonia severity, which reinforces its applicability for patients with different laryngeal diagnoses.